Design and energy performance of PV systems: a case study Kosova - Bylykbashi, Blerina; Hoxha, Bukurije (Institute of Advanced Engineering and Science, 2024)
The energy and environmental crisis are increasing every day. Where the focus of energy production is being driven by renewable energy sources. Solar energy represents an inexhaustible source of energy that can be used almost anywhere. This paper presents the analysis of the energy performance of photovoltaic (PV) and photovoltaic thermal (PVT) panels for the climatic conditions of Kosovo. The site analyzed is the building of the University Clinical Center in Prishtina. The analysis included five types of photovoltaic modules from where the highest energy performance is shown by the PVT panels with a theoretical power produced during July 273 W while during December 78 W. Also, with an efficiency of 59.77% during the month of December and an efficiency of 17.08% during the month of July. While among the other types of PV panels, polycrystalline panels have the best performance with a theoretical power of 252 W during July and 72 W during December. But they showed an efficiency of 48.78 during the month of December and an efficiency of 13.94 during the month of July. The analysis made is presented in an analytical and detailed manner for certain climatic conditions of annual measurements.